Technique For Teaching Speaking At English Department Of Muhammadiyah University Of Surakarta In 2011/2012 Academic Year : A Micro Etnography - Purwono, Trimo, Drs. Djoko Srijono, M.Hum, Dr. Anam Sutopo, M.Hum (2013)
This research aims at describing the teaching learning process on speaking skill at second semester English Department of Muhammadiyah University of Surakarta in 2011/2012 Academic Year. It is conducted to describe the objective of study, teacher technique, the problem faced, and problem solving of English Department of Muhammadiyah University of Surakarta. In this research the data are derived from event, informant, and document. There are three techniques in collecting the data namely: observation, interview, and content analysis. The data achieved from information related to the teaching learning process on speaking 2, in the form of field note, script interview and document related to teaching learning process on speaking skill at English Department of Muhammadiyah University of Surakarta. The results of the study show that 1) There are four techniques used by the teacher in teaching speaking. They are discussion, games, simulation and problem solving techniques. 2) The problems faced by the teacher in teaching learning speaking 2 are management of the class, the capability of the students, and limited time, while problems faced by the students in learning speaking 2 are limited vocabulary, the difficulty of pronunciation, and nervousness. 3) The problems solving used by the teacher to overcome the problem faced by students in learning speaking are the lecturer solve this problem with making a list of vocabulary on their note book.